A CHAOTIC BAT ALGORITHM FOR SOLVING DEFINITE INTEGRAL - AL-Wagih, Khalil (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In this paper, an Improved Bat Algorithm with Chaos (IBACH) is presented for solving definite integral. The IBACH satisfies the question of parallel calculating numerical integration in engineering and those segmentation points that are adaptive. Several numerical simulation results show that the algorithm offers an effective way to calculate numerical value of definite integrals; it has a high convergence rate, a high accuracy and robustness.